Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
 
\begin{equation} {y}'={(10^{-x})}'=10^{-x} \ln 10*{(-x)}'=- \end{equation} \begin{equation} - \ln 10*10^{-x}; \end{equation} \begin{equation} y={(\frac{5^{x}+2}{5^{x}-1})}'= \end{equation} \begin{equation} =\frac{{(5^{x}+2)}'(5^{x}-1)--(5^{x}+2){(5^{x}-1)}'}{(5^{x}-1)^{2}} \end{equation} \begin{equation} =\frac{5^{x} \ln 5(5^{x}-1)-5^{x} \ln 5(5^{x}+2)}{(5^{x}-1)^{2}}= \end{equation} \begin{equation} =\frac{5^{x} \ln 5(5^{x}-1-5^{x}-2)}{(5^{x}-1)^{2}}=-\frac{3*5^{x} \ln 5}{(5^{x}-1)^{2}}; \end{equation}